A new species of Cyllopsis (Lepidoptera: Nymphalidae: Satyrinae) from Costa Rica - Chacón, Isidro; Nishida, Kenji (Revista de Biología Tropical, 2002)
Cyllopsis emilia Chacón and Nishida, a new satyrine species, is described from a single male specimen from Cerro de la Muerte, San José, Costa Rica. This new species can be distinguished from other species of Cyllopsis by its white coloration